PRES in Pediatric HSCT: A Single-Center Experience. Issue 6 (August 2018) - Kapoor, Rajan; Simalti, Ashish; Kumar, Rajiv; Yanamandra, Uday; Das, Satyaranjan; Singh, Jasjit; Nair, Velu
Abstract : Posterior reversible encephalopathy syndrome (PRES) has diverse etiologies and is closely linked to hematopoietic stem cell transplant (HSCT). Headache and seizures are the most common clinical presentations. Although near total recovery is seen in the majority of patients with appropriate management, the implications of its occurrence in the setting of an HSCT is much more than the residual neurological deficits. Graft rejection and occurrence of graft versus host disease has been reported. We analyzed retrospectively our data of 35 pediatric HSCT recipients over the last 2 years at our center. In total, 17% (n=6) patients developed PRES. Headache and seizures were the most common clinical presentations. All patients were on calcineurin inhibitors at the onset of symptoms. The median time after HSCT to the onset of PRES was 21 days. In total, 34% (n=2) patients developed residual neurological deficit. One patient died of acute graft versus host disease at a later date, and 50% (n=3) patients had graft rejection and return to transfusion dependence. The implications of PRES on HSCT outcomes are grave, and better immunosuppression transition protocols need to be developed.